Sistema reprodutivo e diversidade genética de populações naturais de Muricizeiros (Byrsonima crassifolia L. -Kunth) nas savanas de Roraima - Benezar, Rosa Maria Cordovil (2006)
The present work analyzed the reproductive system and the genetic diversity inside and among three natural populations of murici (Byrsonima crassifolia L - Kunth) in the savannahs of Roraima. Three natural populations of murici were evaluated in experimental Field of the EMBRAPA, Cauamé Fields of the Scientific Center of Agrarian (CCA) of the UFRR and Bom Intento. To characterize the reproductive system, 05 experiments, were carried out: spontaneous self-polination, induced self-polination, geitonogamy, natural and xenogamy polination. The genetic diversity was access ed by morphologic characters and by molecular marker RAPD. The results show ed that the muricizeiro presents anthesis diurne whichlasts up to ten hours and the reproductive system showed significant differences between the treatments. The treatment of natural pollination produced ahigher amount of fruits (85%) distingushing from the others. Spontaneous self-polination (5%) differed significantly from geitonogamy (40%) and xenogamy (35%) although the two last treatments have no difference between themselves. There was no significant difference between spontaneous self pollination and auto induced polination, however there were significant differences between auto spontaneous and geitonogamy polination. With reference to the biometry of the fruits there were signficant differences between the types evaluated for the two characteristics, indicating high genetic variability in the evaluated populations and forming five distinct groups in the population of Cauamé. In the analysis of the genetic diversity among and inside populations based on molecular marker, three primers were efficient in discriminating the three populations and demonstrating the great genetic diversity inside and among the populations. The eight primers used FUS-1 was the most polimorphyc.